The Hand Mirror Image: Which is the Lineage in the End? - Bapat, Kalyani N; Patil, Rajesh B (Annals of Pathology and Laboratory Medicine, 2021)
According to the World Health Organization (WHO) 2016 classification, acute promyelocytic leukemia (APL) is placed in the category of AML with recurrent cytogenetic abnormalities. Cytogenetic confirmation of reciprocal translocation t(15:17) is essential criteria for diagnosis of this entity. However, these tests may have a significant time delay and it is usually the characteristic morphology of the abnormal promyelocytes which helps to pick up the diagnosis early and alert the clinician to initiate treatment promptly. The two variants commonly described are the hypergranular and the variant (M3v) forms, but knowledge of other rarer morphological variants of APL becomes crucial in certain situations for the hematopathologist. To highlight this phenomenon, we describe a case report of a 9-year-old female who presented with a hand mirror morphology of the abnormal promyelocytes.